2023
DOI: 10.3390/pharmaceutics15020490
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the In Vivo Transdermal Bioavailability of Asenapine Maleate Using Novel Lavender Oil-Based Lipid Nanocapsules for Management of Schizophrenia

Abstract: Lipid nanocapsules (LNCs) are promising for transdermal drug delivery due to their higher permeability-enhancing effects compared to polymeric nanoparticles. Lavender oil is an essential oil consisting of several terpenes (primarily linalool and linalyl acetate) known for their profound permeation-enhancing action. In the present work, we successfully encapsulated asenapine maleate (a second-generation antipsychotic that is highly metabolized by the liver, reducing its oral bioavailability) into biocompatible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It is evident that polymeric nanoparticles, especially those having a particle size less than 100 nm and carrying a charge, are an excellent choice for the treatment of inflammatory skin disorders due to the selective accumulation in the inflamed skin [ 136 , 137 , 138 ]. On the other side, lipidic systems such as lipid nanoemulsions and nanocapsules tend to enhance the transdermal permeation of the encapsulated drugs due to their greater ability to diffuse through the different skin layers [ 139 , 140 ]. Therefore, polymeric nanocapsules containing natural oils would offer an excellent candidate for topical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that polymeric nanoparticles, especially those having a particle size less than 100 nm and carrying a charge, are an excellent choice for the treatment of inflammatory skin disorders due to the selective accumulation in the inflamed skin [ 136 , 137 , 138 ]. On the other side, lipidic systems such as lipid nanoemulsions and nanocapsules tend to enhance the transdermal permeation of the encapsulated drugs due to their greater ability to diffuse through the different skin layers [ 139 , 140 ]. Therefore, polymeric nanocapsules containing natural oils would offer an excellent candidate for topical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the proportion of LAV in LNC resulted in a decrease in PS with an increase in PDI but the difference was only statistically significant (p ≤ 0.05) when the proportion of LAV exceeded that of Labrafac (1:2; Labrafac: LAV ratio, F4). El-Tokhy et al, [65] previously reported smaller PS for LNC with Lavander essential oil oily core compared to Labrafac. This was attributed to Lavender oil low viscosity and low oil/water interfacial tension in addition to its polarity and hence ability to form nanoemulsions by the phase-inversion method [65].…”
Section: Colloidal Propertiesmentioning
confidence: 95%
“…El-Tokhy et al, [65] previously reported smaller PS for LNC with Lavander essential oil oily core compared to Labrafac. This was attributed to Lavender oil low viscosity and low oil/water interfacial tension in addition to its polarity and hence ability to form nanoemulsions by the phase-inversion method [65].…”
Section: Colloidal Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Its analgesic effect is due to the content of compounds such as linalool and linalyl acetate, which have the ability to block the transmission of pain signals within the peripheral nervous system [ 27 , 28 , 29 ]. Moreover, previous studies have demonstrated the potential of lavender essential oil as an effective carrier for drug delivery, enhancing the permeation and therapeutic efficacy of various pharmaceuticals, such as asenapine maleate [ 30 ], penciclovir [ 31 ], lidocaine, caffeine [ 32 ], and p-aminobenzoic acid [ 18 ]. The use of essential oils such as clove, cinnamon, cyperus, chuanxiong, angelica, and turpentine [ 13 , 17 , 33 ] in increasing ibuprofen’s bioavailability is also known.…”
Section: Introductionmentioning
confidence: 99%